2013
DOI: 10.1371/journal.pgen.1003787
|View full text |Cite
|
Sign up to set email alerts
|

Meiotic Recombination in Arabidopsis Is Catalysed by DMC1, with RAD51 Playing a Supporting Role

Abstract: Recombination establishes the chiasmata that physically link pairs of homologous chromosomes in meiosis, ensuring their balanced segregation at the first meiotic division and generating genetic variation. The visible manifestation of genetic crossing-overs, chiasmata are the result of an intricate and tightly regulated process involving induction of DNA double-strand breaks and their repair through invasion of a homologous template DNA duplex, catalysed by RAD51 and DMC1 in most eukaryotes. We describe here a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

30
186
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 118 publications
(216 citation statements)
references
References 66 publications
(104 reference statements)
30
186
0
Order By: Relevance
“…Matching the previously reported localization patterns after DNA damage (Da Ines et al , 2013b), we found that RAD51 builds foci in the nuclei of root cells after treatment with cisplatin as seen with an antibody raised against RAD51 (Fig 5D and E). These foci depend on the presence of the checkpoint kinase ATM and to a lesser degree on ATR activity while they are absent, as expected, in the rad51 mutant (Fig 5D).…”
Section: Resultssupporting
confidence: 91%
See 3 more Smart Citations
“…Matching the previously reported localization patterns after DNA damage (Da Ines et al , 2013b), we found that RAD51 builds foci in the nuclei of root cells after treatment with cisplatin as seen with an antibody raised against RAD51 (Fig 5D and E). These foci depend on the presence of the checkpoint kinase ATM and to a lesser degree on ATR activity while they are absent, as expected, in the rad51 mutant (Fig 5D).…”
Section: Resultssupporting
confidence: 91%
“…Homology search and strand invasion are performed by RAD51 family members (Serra et al , 2013), the eukaryotic homolog of the E. coli recA protein (Mengiste & Paszkowski, 1999). RAD51 has five paralogs in Arabidopsis (RAD51B, RAD51C, RAD51D, XRCC2, and XRCC3), all of which function in HR in somatic or meiotic cells and show fewer homologous recombination events after DNA damage (Abe et al , 2005; Da Ines et al , 2013a,b; Serra et al , 2013), which is in line with studies in other eukaryotes (Hosoya & Miyagawa, 2014). …”
Section: Introductionsupporting
confidence: 74%
See 2 more Smart Citations
“…Work in Saccharomyces cerevisiae and Arabidopsis has established that Rad51 is needed for Dmc1 filament formation, and one model posits that Rad51 serves to initiate a Dmc1 filament (4,21,22). In our previous work, we showed that BRC1-4 bind with high affinity to free RAD51, enhancing ssDNA assembly and limiting its nucleation on dsDNA, resulting in a stimulation of DNA strand exchange.…”
Section: Brca2 Stimulates the Dna Strand Exchange By Dmc1 Overcomingmentioning
confidence: 91%